Community science data suggest the most common raptors (Accipitridae) in urban centres are smaller, habitat‐generalist species. (16th February 2022) - Cooper, Daniel S.; Shultz, Allison J.; Şekercioğlu, Çağan H.; Osborn, Fiona M.; Blumstein, Daniel T.
Abstract : As the world becomes more urbanized, identifying traits that allow some species to thrive in cities will be key to predicting which species will probably remain common and which may require conservation attention. Large, diverse, widely distributed and readily documented raptors represent an ideal taxonomic group to understand how species persist and thrive in urban areas. Global community science datasets can reveal patterns that might be obscured in studies limited to a small number of locations, those relying on presence/absence data or those conducted by a small number of observers. We analysed 127 species of raptors (hawks and related species; Family: Accipitridae) using recent community‐science (eBird) records from 59 cities on five continents, modelling two indices of occurrence with five ecological and life history traits, and incorporating phylogenetic relatedness. Based on previous studies of avian traits in urban vs. rural populations, and well as our casual observations of birds in cities across the USA and around the world, we hypothesized that urban raptor communities would be dominated by smaller, ecological‐generalist species regardless of the regional species pool. We defined urban occurrence in two ways: urban abundance (the frequency of breeding season reports within 10 km of a city centre) and species proportion (the relative abundance of each species in the local raptor community). We did not detect a strong phylogenetic signal for either urban occurrence index, suggesting that various unrelated raptor species may become common in cities of the world. In the best‐performing models, both urban indices were significantly negatively associated with body mass, and significantly positively associated with habitat breadth; species proportion was also significantly associated with nest substrate breadth. Our analysis suggests that there may be an 'archetypal urban raptor' and that species lacking these traits (e.g. large, specialist taxa) may be at greater conservation risk as global urbanization increases.